Debt Report 2022 : Edition II - World Bank (Washington, DC, 2022)
This is the second of the series of Debt Reports for 2022 to be published online and provide users with data and analysis on external and public debt of low- and middle-income countries. Debt Report 2022 second edition presents preliminary estimates of external debt stocks at end-2021 for low- and middle-income countries and information on new bond issuance in international capital markets in 2021. The report also provides an update on new initiatives to enhance debt transparency and broaden the coverage of the debt data collected and disseminated by the World Bank.